LITERATUR REVIEW: PENGARUH YOGA DAN OBAT HERBAL PADA SAAT MENOPAUSE: LITERATURE REVIEW: INFLUENCE OF YOGA AND HERBAL MEDICINE AT MENOPAUSE - Sunarsih, Tri Sunarsih; Annisa Alfitri; Erni Kurniawati; Nurviyanti Octavia (Intan Husada : Jurnal Ilmiah Keperawatan, 2024)
Background: Menopause is a natural phase in a woman's life which is marked by the permanent cessation of menstruation. During menopause, significant hormonal changes occur in a woman's body, which can cause certain symptoms and health effects. In an effort to reduce symptoms and maintain health holistically, many women seek alternative treatments such as yoga and the use of herbal medicine. Purpose: To determine the effect of yoga and herbal medicine on menopausal hypertension. Method: used in writing this article is a literature review. Namely a literature search both international and national which was carried out using the Google Scholar database, National Library of Indonesia, Mendeley, PubMed. In the early stages of journal articles, 354 articles were obtained from 2018 to 2022 using the keywords "Complementary Services in menopause" and "Yoga for Menopause" identified which have not yet explored the relevance of the articles to be compiled. Results: In terms of the effectiveness of yoga can reduce complaints of manopausal syndrome in menopausal women which can improve the quality of life of menopause then in the aspect of herbal medicine for menopause it is more towards treating diseases in menopause, such as giving celery juice a combination of carrots and honey which is proven to reduce hypertension in menopausal women and there is a recommendation to give avocado smoothie. Those with hypertension Manopausal symptoms and the quality of life of women during menopause are inseparable concepts. Therefore, women's quality of life greatly affects the severity of symptoms at the time of menopause. Conclusion: By consuming herbal medicine and yoga which can be a positive hobby, it will increase women's productivity and reduce diseases and symptoms that arise during menopause.